Development of a Method to Monitor Gene Expression in Single Bacterial Cells During the Interaction With Plants and Use to Study the Expression of the Type III Secretion System in Single Cells of Dickeya dadantii in Potato - Cui, Zhouqi; Yuan, Xiaochen; Yang, Ching-Hong; Huntley, Regan B.; Sun, Weimin; Wang, Jie; Sundin, George W.; Zeng, Quan (Frontiers in Microbiology, 2018)
Dickeya dadantii is a bacterial plant pathogen that causes soft rot disease on a wide range of host plants. The type III secretion system (T3SS) is an important virulence factor in D. dadantii. Expression of the T3SS is induced in the plant apoplast or in hrp-inducing minimal medium (hrp-MM), and is repressed in nutrient-rich media. Despite the understanding of induction conditions, how individual cells in a clonal bacterial population respond to these conditions and modulate T3SS expression is not well understood. In our previous study, we reported that in a clonal population, only a small proportion of bacteria highly expressed T3SS genes while the majority of the population did not express T3SS genes under hrp-MM condition. In this study, we developed a method that enabled in situ observation and quantification of gene expression in single bacterial cells in planta. Using this technique, we observed that the expression of the T3SS genes hrpA and hrpN is restricted to a small proportion of D. dadantii cells during the infection of potato. We also report that the expression of T3SS genes is higher at early stages of infection compared to later stages. This expression modulation is achieved through adjusting the ratio of T3SS ON and T3SS OFF cells and the expression intensity of T3SS ON cells. Our findings not only shed light into how bacteria use a bi-stable gene expression manner to modulate an important virulence factor, but also provide a useful tool to study gene expression in individual bacterial cells in planta.